Diagnostic role of rapid urinary trypsinogen-2 strip test in acute pancreatitis - Jain, Meenal; Sundaresan, Vinoth; Gowthaman, Siddhartha; Manickam, Ramanathan (International Surgery Journal, 2021)
Acute pancreatitis is one of the most common surgical conditions that present with acute abdomen. Serum amylase and lipase are one of the most important and widely used laboratory methods to diagnosis acute pancreatitis. However, these tests have had unsatisfactory results in terms of their sensitivity and specificity. Urinary trypsinogen-2 strip test has been developed for the detection of increased levels of trypsinogen-2 in urine and has been suggested to play an important role in the screening of aucte pancreatitis on the basis of its rapid results. In this review, we aimed to assess the diagnostic role of the same existing articles using databases like pubmed, google scholar, medline, pubmed central. We analysed about 50 articles all of which were in English and 15 were excluded on the basis of our subject criteria.